Perhatian Orang Tua Terhadap pembelajaran Bahasa Arab Peserta Didik di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar - Kurniawan Kurniawan (Diwan : Jurnal Bahasa dan Sastra Arab, 2018)
The objectives of the study were to indentify: 1) How is the Arabic learning at Makassar smart integrated Islamic Elementary school? 2) what are the forms of parental concern in Arabic learning at Makassar smart integrated Islamic elementary school? 3) what is the impact of parental concern on the students’ Arabic learning at Makassar Smart Integrated Islamic Elementary school?. The study was qualitative research using the normative-thelogical,pedagogical, and linguistiq approaches. The data sources were parents of student, Arabic teachers, principal, and students. Furthermore, observation, interview, and documentation  were utilized in collecting the data, which then processed and analyzed through the the three stages of data reduction, data presentation, and conclusion drawing. The results of the study revealed that the Arabic learning at Makassar smart integrated Islamic elementary school was carried out by memorizing basic vocabulary such as parts of the body, plants, and other projected using visual media of images/photos.Furthermore there were two forms of parental concern on the students’ Arabic  learning at Makassar smart integrated Islamic elementary school, namely: 1) playing the basic Arabic language learning videos which were at least in line with the Arabic language material taught to the student at school, 2) motivating student to be determined in learning Arabic. In addition, the impact of parental concern on the students’ Arabic learning at Makassar smart integrated Islamic elementary school consisted of two impact, positive and negative. The first positive impact, the students’ knowledge of Arabic was constantly developing and the second was students repeated the Arabic they had learned at home. Whereas the negative impact was the teaching burden entirely based on the Arabic teachers.Keyword: Parents, Arabic teacher, Arabic learningAbstrakTujuan penelitian ini yaitu untuk mengetahui: 1) Bagaimana pembelajaran bahasa Arab di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar, 2) bagaimana bentuk-bentuk perhatian orang tua terhadap pembelajaran bahasa Arab peserta didik di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar, serta 3) bagaimana dampak perhatian orang tua terhadap pembelajaran bahasa Arab peserta didik di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar. Jenis penelitian ini tergolong kualitatif dengan pendekatan penelitian yang digunakan adalah: teologi-normatif, pedagogis dan linguistik. Adapun sumber data penelitian ini adalah orang tua peserta didik, guru bahasa Arab, Kepala Sekolah, dan peserta didik. Selanjutnya, metode pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Lalu teknik pengolahan dan analisis data dilakukan dengan melalui tiga tahapan, yaitu: reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pembelajaran bahasa Arab di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar dengan menghafal kosa kata-kosa kata dasar seperti anggota badan, tanam-tanaman dan lain sebagainya yang diproyeksikan dengan menggunakan media visual gambar/foto. Selanjutnya terdapat terdapat dua bentuk perhatian orang tua terhadap pembelajaran bahasa Arab peserta didik di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar, yaitu: 1) mempertontonkan video pembelajaran bahasa Arab dasar yang sedikitnya selaras dengan materi bahasa Arab yang diajarakan pada peserta didik di sekolah, dan 2) memotivasi peserta didik untuk tekun dalam belajar bahasa Arab. Kemudian dampak dari perhatian orang tua terhadap pembelajaran bahasa Arab di Sekolah Dasar Islam Terpadu (SDIT) Smart School Makassar yaitu terdiri dari dua dampak, positif dan negatif. Dampak positif pertama, pengetahuan bahasa Arab peserta didik senantiasa berkembang dan kedua peserta didik mengulang kembali bahasa Arab yang telah dipelajarinya di rumah. Kemudian dampak negative yang ditimbulkan yaitu beban mengajar tertumpu sepenuhnya pada guru bahasa Arab.